Penegakan Hukum Terhadap Kejahatan Terorisme Dalam Hukum Pidana Internasional - Ariantoa, Mey Navo Refry (Jurnal JURISTIC, 2024)
This research aims to discuss the position of terrorism in international criminal law and law enforcement against terrorist crimes. The research method used in this research is the normative juridical legal research method. In several literatures, terrorism crimes in international criminal law are categorized as extraordinary crimes because of their systematic, organized and widespread nature. Law enforcement against crimes of terrorism can basically be carried out by means of preventive action as a preventive action and repressive action as a penalty action, which in this case can be prosecuted based on the legal rules of the country of origin of the perpetrator and it is permissible to carry out preventive actions. arrest, prosecution and punishment or probation. Extradition if necessary. Apart from that, law enforcement based on international criminal law can also be sought if the crime of terrorism committed by the perpetrator has an impact on the international community and meets the requirements as stipulated in the Rome Statute.